Sosialisasi Perencanaan Pembangunan Kampung Bagi Mahasiswa Peserta KKN Tahun 2018 Fakultas Ekonomi Dan Bisnis Universitas Cenderawasih - Marsi Adi Purwadi (The Community Engagement Journal, 2018)
The objectives of the Village Development Planning Socialization Activities for Students of the Year 2018 KKN Participants are the Faculty of Economics and Business, University of Cenderawasih are: 1) Increased knowledge of participants about the village development planning process in accordance with applicable regulations; 2) Increasing participants' knowledge about planning models that can be applied in the village development planning process; 3) Increased participants' knowledge about synchronization and consistency between planning, budgeting, implementing, and monitoring government programs from village to district levels. The method of applying science and technology is to carry out seminars with adult learning methods. The results of the implementation of this activity indicate that there was an increase in the training participants' ability / understanding by 24.65 percent related to 1) the village development planning process in accordance with applicable regulations; 2) planning models that can be applied in the village development planning process; and 3) synchronization and consistency between planning, budgeting, implementing, and monitoring government programs from the village to the district level. As many as 96 percent of participants attended the training, while 2 percent did not attend training.